An Exploration Of Banks' Managers' Perceptions Towards Equity-based Financing Practices In Malaysia - Siti Nor Amira Mohamad; Mohamad Yazis Ali Basah; Muhammad Ridhwan Ab. Aziz (Academic Inspired Network, 2024)
The aim of this paper is to explore the banks' managers’ perceptions towards equity-based financing practices in Malaysia. The study uses qualitative approach to explore in detail their perceptions as well as the experiences towards equity-based financing practices in Islamic banking approach. In-depth interviews with Islamic banks’ managers in Malaysia and thus phenomenological strategies are used in analyzing the data. It is concluded that the interviewees have considerable perceptions towards equity-based financing practices and this paper proposed the future work of research.